The effects of financial aid and returns information in selective and less selective schools: Experimental evidence from Chile - Matías Busso; Taryn Dinkelman; Claudia Martínez Alvear; Dario Romero (Inter-American Development Bank (IDB), 2016)
Schools that provide higher education often belong to either a merit-based selective system or an open-access less selective system. This paper presents the results of a field experiment that provided Grade 12 students in Chile with tailored information about financial aid and average earnings and employment probabilities for schools and careers in both types of schools. No effect is found on the extensive margins of enrollment in the selective or in the less selective sector. Treated students change their intensive margin decisions: they choose careers and schools with lower expected wages and lower employment probabilities, but with higher quality relative to their baseline preferences.
hdl:11319/7937
Keywords: I23; I22; I26; D83; 330; Information experiment; Higher education; Financial aid; Returns to education; Chile